Logical Modeling and Analysis of Cellular Regulatory Networks With GINsim 3.0 - Naldi, Aurélien; Hernandez, Céline; Abou-Jaoudé, Wassim; Monteiro, Pedro T.; Chaouiya, Claudine; Thieffry, Denis (Frontiers in Physiology, 2018)
The logical formalism is well adapted to model large cellular networks, in particular when kinetic data are scarce. This tutorial focuses on this well-established qualitative framework. Relying on GINsim (release 3.0), a software implementing this formalism, we guide the reader step by step towards the definition, the analysis and the simulation of a four-node model of the mammalian p53-Mdm2 network.